Measuring the Economic Impact of Climate Change on Ethiopian Agriculture : Ricardian Approach - Deressa, Temesgen Tadesse (World Bank, Washington, DC, 2012)
This study uses the Ricardian approach to analyze the impact of climate change on Ethiopian agriculture and to describe farmer adaptations to varying environmental factors. The study analyzes data from 11 of the country's 18 agro-ecological zones, representing more than 74 percent of the country, and survey of 1,000 farmers from 50 districts. Regressing of net revenue on climate, household, and soil variables show that these variables have a significant impact on the farmers' net revenue per hectare.The study carries out a marginal impact analysis of increasing temperature and changing precipitation across the four seasons. In addition, it examines the impact of uniform climate scenarios on farmers' net revenue per hectare. Additionally, it analyzes the net revenue impact of predicted climate scenarios from three models for the years 2050 and 2100. In general, the results indicate that increasing temperature and decreasing precipitation are both damaging to Ethiopian agriculture. Although the analysis did not incorporate the carbon fertilization effect, the role of technology, or the change in prices for the future, significant information for policy-making can be extracted.